THE POTENTIAL BENEFITS OF TEACHING ENGLISH LITERATURE IN EFL CLASSROOM CONTEXT - , Sunardi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract Generally, this article aims at familiarizing to teachers who teaching English about essential roles of English literature in language classroom practices. While some teachers may still believe that teaching literature in EFL context encompasses focusing on linguistics competence only. Others who have integrated literature in the curricula have realized that literature has more dimensions other than linguistics that it may have. The main purpose of this article is to introduce several models of literature teaching models and to describe how those teaching models contribute to the language teaching for practical purposes. The reawakening of interest in literature will bring educational or pedagogical in EFL context. In the context of language teaching, literature contributes to three main aspects; linguistic competence; cultural competence; and personal growth. These three main points would be the models for teaching language that would elaborated further on this article. In term of Linguistic model, the teaching is directed to the acquisition of language since the language is the main medium of literature. In addition, linguistic acquisition is believed to be able to bring the students to understand literary works. For cultural model, the teaching focuses on cross cultural understanding; while in the personal growth model, students are expected to combine the two competencies that the two previous models expected to have. At the end, this article is expected to provide suggestions and pedagogical implication of literature teaching practices to teachers who have the relevant field of interest.